Expansion of the agenda for human rights : feminist perspectives - Antrobus, Peggy (Bridgetown: Women and Development Unit, 1995)
Traces the movement of feminist initiatives through several major UN conferences in the 90s. Calls for more involvement of Caribbean women in human rights's issues since women's rights and human rights are inextricably linked.